Analysis Of Student Learning Interest In Science Subjects Class V Di Muhammadiyah Elementary School 02 Medan - Andini, Rita; Abill, Sayla Baqdain (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
This study aims to analyze students' interest in learning science. Interest is Wrong One aspect psychic man Which can push For reach objective. Someone who has an interest in an object, tends to pay attention or feel greater pleasure for the object. Teacher's strategy in increasing interest Study participant educate is give participant educate For take decision as well as control, give a clear instruction, create a threat-free classroom environment, change the atmosphere learning, offer various learning models and methods, create fair competition positive, offer present, give not quite enough answer to participant educate, give chance for students to study in groups, encourage them to self-reflect, enthusiastic, get to know students, know the interests of students, help students to find motivation from in himself. Type study This is use study qualitative descriptive. The location of this research is SD Muhammadiyah 02 Medan, Jl. Mustafa No.1 Glugur Darat I, Kec. East Medan, Medan City, North Sumatra. Research subjects are participants educate. Instrument study Which used is interview, And observation. Then then the number of population or informants in this study consisted of 30 students. Sample used in this study consisted of 5 students of class VA. The results of this study is that researchers can analyze how students' interest in learning science, and what teacher's strategy is suitable for learning science: (1) students prefer learning science done outside class or done practice in a manner direct. (2) student very like science learning because it relates to the environment and everyday life. (3) at the moment learning going on what good Teacher use media Study in present the material so that it becomes more enthusiastic and fosters interest in student learning. (4) students feel bored when learning is done only with the lecture method because it is difficult understood and easily bored, (5) if they feel bored, they tend to choose to play and class noise. Thus, the observations or analyzes carried out at SD Muhammadiyah 02 Medan, teachers must be more active, creative and innovative in the ongoing learning process especially on science learning.Keywords: Interest Study student, Learning science, Strategy Teacher